2008
DOI: 10.1021/ma801660x
|View full text |Cite
|
Sign up to set email alerts
|

Kumada Catalyst-Transfer Polycondensation of Thiophene-Based Oligomers: Robustness of a Chain-Growth Mechanism

Abstract: Synthesis.2-Bromo-3-hexyl-5-iodothiophene (6). NBS (37.38g, 0.21 mol) was added to the solution of 3hexylthiophene (33.66 g, 0.2 mol) in 500 mL of a chloroform-acetic acid mixture (50/50 v/v) in the absence of light, under an argon atmosphere, at temperature 0°C. The mixture was allowed to reach room temperature, and stirred overnight, and hydrolyzed with 500 mL of ice-water, and the aqueous phase extracted with chloroform. The combined extracts were washed with water, 1 M sodium hydroxide solution (50 ml), ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 37 publications
8
142
0
Order By: Relevance
“…Thus, KCTP not only follows the chain-growth mechanism but even displays the characteristics of a ''living'' polymerization process. [62] While we and several other research groups have confirmed the chain-growth mechanism for the KCTP of 1 [22,24,63,64] and other monomers, [28][29][30][31][65][66][67] Achord and Rawlins [68] reported data that contradict the observations of the livingness of KCTP. [24,69] General Mechanism…”
Section: Assessment Of the Chain-growth Mechanismmentioning
confidence: 52%
See 3 more Smart Citations
“…Thus, KCTP not only follows the chain-growth mechanism but even displays the characteristics of a ''living'' polymerization process. [62] While we and several other research groups have confirmed the chain-growth mechanism for the KCTP of 1 [22,24,63,64] and other monomers, [28][29][30][31][65][66][67] Achord and Rawlins [68] reported data that contradict the observations of the livingness of KCTP. [24,69] General Mechanism…”
Section: Assessment Of the Chain-growth Mechanismmentioning
confidence: 52%
“…The first ex situ prepared Ni initiators were synthesized by Senkovskyy et al starting from Ni(PPh 3 ) 4 , which undergoes oxidative addition with various arylhalides such as bromobenzene or orthobromotoluene, to give the desired adducts Ar-Ni(PPh 3 ) 2 -Br (Scheme 3a). [44,65] It was found that KCTP of 1 initiated by these complexes proceeds via chain-growth and led to regioregular P3HT with a relatively broad polydispersity of %1.6. Almost 100% of the initiator Ar-group was incorporated into the polymer for DPs smaller than 30, as evidenced by 1 H NMR and MALDI-ToF analysis.…”
Section: Ex Situ (External) Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been shown by KCTPpolymerization of bi-and terthiophene, that the chain-growth polymerization is maintained for longer monomer units, however with higher chain-transfer probabilities and, resultantly, a decreased controlled character. 73 In the case of CPDT, however, our experiments indicate that transfer and termination reactions occur only limited during the polymerization. Furthermore, after a full conversion of the first CPDT-equivalent (after 20 min), all growing polymer chains remain active and continue to grow after a second equivalent is added.…”
Section: Homopolymerizationmentioning
confidence: 66%